PENGENDALIAN INTERN PENGELOLAAN SUMBER DAYA SEKOLAH DALAM UPAYA MENJAMIN LAYANAN BELAJAR YANG BERKUALITAS PADA SMP SWASTA NURUL ARAFAH BAKTIYA ACEH UTARA - Muhammad, Nasir (Universitas Islam Negeri (UIN) Sumatera Utara, 2022)
This research explains the internal control system and its linkage in ensuring quality learning services at private SMP Nurul Arafah Baktiya North Aceh. The method used is qualitative with the technique of collecting interview data, observation and documentation. The result of the research shows that internal control of school resource management at Nurul Arafah Baktiya Junior High School of North Aceh is done by setting performance standard through principal leadership competence, pedagodic competence, personality competence and social competence as well as teacher professionalism. In addition, supervisors also measure performance by providing performance appraisals, establishing irregularities such as corrupt practices, collusion and nepotism, and providing school development recommendations and problem solving. Internal controls have a good influence on the management of school resources to create quality learning services proven through the effectiveness of teaching and learning processes that are able to internalize science in life, have good principal leadership competence in managing and deciding a policy that can support the education system The quality of the school, then the realization of a healthy school environment, orderly and comfortable for learners with adequate facilities and infrastructure. The principal also has an effective ability in the management of educational personnel to realize the professionalism of educational personnel by providing rewards for educational personnel who excel.